1992
DOI: 10.1002/jcla.1860060512
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot assay for detection of autoantibodies in autoimmune disease

Abstract: When detecting antinuclear antibodies (ANA) a similar indirect immunofluorescence (IIF) pattern may be produced by antibodies which correspond to different antigenic specificity or to diverse autoimmune disorders. To circumvent this problem, we used an immunoblotting against total antigen from HEp-2 cells (TA-HEp-2-C) which proved to be more specific and sensitive than IIF, since it detected up to 40 antigenic bands and an immunoblot pattern characteristic of each individual and unrelated to the fluorescence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Autoimmune disease is a clinical condition in which immune responses are abnormally activated and negative regulation of the immune system is repressed . It has been recently reported that abnormalities in both the number and function of CD4 + CD25 + regulatory T cells (Tregs) can reduce regulatory restraint and result in the hyperproliferation of psoriatic pathogenic T cells …”
mentioning
confidence: 99%
“…Autoimmune disease is a clinical condition in which immune responses are abnormally activated and negative regulation of the immune system is repressed . It has been recently reported that abnormalities in both the number and function of CD4 + CD25 + regulatory T cells (Tregs) can reduce regulatory restraint and result in the hyperproliferation of psoriatic pathogenic T cells …”
mentioning
confidence: 99%
“…The immunological screening consisted of ANA and anti-extractable nuclear antibody (anti-ENA) profile that included 15 disease-specific autoantibodies against nucleo-ribonucleoprotein (nRNP/Sm) (mixed connective tissue disease), Sm antibody (SLE), centromere protein B (CENP-B) (systemic sclerosis), proliferating cell nuclear antigen (PCNA) (SLE), dsDNA (SLE), nucleosomes (SLE), histones (SLE), ribosomal P-proteins (SLE), Ro-52 (SS-A) (Sjogren’s syndrome), SS-B (Sjogren’s Syndrome), Scl-70/PM-Scl-100 (systemic sclerosis), Jo-1 (myositis), and anti-mitochondrial M2 antibody (AMA M2) (primary biliary cirrhosis) [21]. ANA was analyzed using indirect immunofluorescence on HEP-2 cell monolayers, and anti-ENA was analyzed by immunoblot assay (Euroimmun, Germany) [22]. The sensitivity and specificity of the methods employed in detection of these antibodies are around 89.06 and 99.71%, respectively [23].…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was carried out as described by Laemmli (21), using 1.5 mm thick 18 x 16 cm plates. Electrophoresis and immunoblotting were performed under the same conditions as previously described (13). The peroxidase conjugate goat anti-human IgG+IgA+IgM (Zymed) was used at a 1 :2,000 concentration, incubated 18 hours at 4°C in agitation, washed with 0.3% PBS Tween 20, developed with 4-chloro-l-naphtol (Sigma) and perhydrol (Merck), rinsed 1 hour in distilled water, and dried on filter paper.…”
Section: Western Blotmentioning
confidence: 99%
“…Thus, IIF for ANA with HEp-2 cells is an important diagnostic tool, since it allows the detection of a larger amount of autoantibodies. It has, however, limited specificity since its ANA and Western blot patterns do not correspond even when the same antigen is used as a substrate (13). Therefore, we have tried to characterize by Western blot the association between different autoantibodies in autoimmune diseases using not only one, but all antigens found in a total HEp-2 cell extract (THEp-2CE).…”
Section: Introductionmentioning
confidence: 99%